EFFECTIVENESS VALIDATION ON EXISTING DESIGN EQUATIONS FOR THE SUSTAINABLE DESIGN OF MASONRY BUILDING RETROFITS - Xavier Langit, Ujan; Abdul Razak, Abdul Karim; Norazzlina, M.Sa'don; Xin Yao, Teng; Pierre, Quenneville; Nur Liza, Rahim (Penerbit UMT, 2022)
Due to the unsatisfactory performance of MS544-5 in estimating the design capacity of bolted timber connections, this present study was initiated to validate the existing predictive equations used by the Malaysian Standard (MS544-5). An evaluation of the European Yield Model (EYM) equation was also done to provide an optimal design equation for the bolted connection design in local hardwood. To verify these two sets of equations, a series of bolted timber connection tests was conducted on Nyatoh hardwood. Nyatoh was chosen as its strength makes it ideal for use as structural timbers, either as roof rafters or floor joists in masonry building constructions. The bolted timber connection tests conducted involved eight types of bolt configurations and the tests on each configuration was done in sets of 10 specimens. The experimental values obtained were then compared with the predictive equations of MS544-5 and EYM to examine their effectiveness. From the comparison, it was found that the prediction values given by MS544-5 were overly conservative with an average effective ratio of 0.34 while the EYM had an average effective ratio of 1.09. Thus, the use of EYM equations was recommended for the sustainable retrofit design development of Malaysian masonry buildings.